2023
DOI: 10.3389/ffgc.2022.1095185
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Asian chestnut gall wasp (Dryocosmus kuriphilus) on chestnut tree growth may be mediated by site resources

Abstract: IntroductionThe Asian chestnut gall wasp (Dryocosmus kuriphilus) is a major pest of chestnut trees worldwide, seriously affecting chestnut cultivation. Information concerning the effects of gall wasp attack on diameter growth of chestnut trees is currently scarce and limited to coppice stands and to use of the growth of a non-target control species (unaffected by the pest) for reference purposes. The effects of the pest on widely-spaced plantations (grown at a much lower density than chestnut coppices) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Figure 6. Distribution of species by months Among the harmful insects found in this study, the Asian chestnut gall wasp, Dryocosmus kuriphilus is an alien species to Europe and attacks species of the genus Castanea worldwide (EFSA, 2010;Castedo-Dorado et al, 2023). In Türkiye, D. kuriphilus was detected for the first time in Yalova in 2014 (Çetin et al, 2014) then it has been expanded its geographical ranges and reported from different provinces of Yalova, Bursa, İstanbul, Sakarya, Kocaeli, Balıkesir, Bilecik, Düzce, Giresun, Bartın, Zonguldak, Sinop and İzmir (Mıcık & İpekdal, 2021;Yıldız et al, 2020).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 6. Distribution of species by months Among the harmful insects found in this study, the Asian chestnut gall wasp, Dryocosmus kuriphilus is an alien species to Europe and attacks species of the genus Castanea worldwide (EFSA, 2010;Castedo-Dorado et al, 2023). In Türkiye, D. kuriphilus was detected for the first time in Yalova in 2014 (Çetin et al, 2014) then it has been expanded its geographical ranges and reported from different provinces of Yalova, Bursa, İstanbul, Sakarya, Kocaeli, Balıkesir, Bilecik, Düzce, Giresun, Bartın, Zonguldak, Sinop and İzmir (Mıcık & İpekdal, 2021;Yıldız et al, 2020).…”
Section: Resultsmentioning
confidence: 97%
“…In Türkiye, D. kuriphilus was detected for the first time in Yalova in 2014 (Çetin et al, 2014) then it has been expanded its geographical ranges and reported from different provinces of Yalova, Bursa, İstanbul, Sakarya, Kocaeli, Balıkesir, Bilecik, Düzce, Giresun, Bartın, Zonguldak, Sinop and İzmir (Mıcık & İpekdal, 2021;Yıldız et al, 2020). It has been reported that heavy gall wasp infestations can reduce chestnut production by up to 80% (Battisti et al, 2014;Castedo-Dorado et al, 2023).…”
Section: Resultsmentioning
confidence: 99%